Leadership Support of Supervision in Social Work Practice: Challenges and Enablers to Achieving Success - Vito, Rosemary (Canadian Social Work Review / Revue canadienne de service social)

(untitled) (Canadian Association for Social Work Education / Association canadienne pour la formation en travail social (CASWE-ACFTS), 2015)
This article discusses research findings that highlight the importance of leadership support of supervision for social workers in human service organizations. While supervision is considered a cornerstone of social work practice, whether and how such supervision is supported by human service leaders is not adequately analyzed. Using qualitative research data from interviews with supervisors and managers in southern Ontario, this article presents the vital role social work leaders play in supporting supervision by modelling values, and creating a safe organizational culture. The challenges of providing this support are also discussed in the current context of new public management. The article concludes with a series of recommendations, including: prioritizing supervision to promote organizational learning, organizational restructuring to reduce power differentials, modelling social work values to create a safe learning culture, and supporting supervisory and leadership training for social workers. Findings may be of interest to social workers who are leading, supervising, teaching or practicing in human service organizations.